Opportunities and Challenges of Using Community-based Pedagogy to Foster Meaningful Learning of English in a Context of Escuela Nueva (2023)
ABSTRACT : This report chronicles the experience a pre-service teacher had with her ten mixed-grader students gathered in a context of Escuela Nueva Model, in a rural school located in El Carmen de Viboral, Antioquia. The preliminary observations did not display any community participation for English classes, even if it was stated as an essential statute in the school’s pedagogical project and in the pedagogical model. In addition, English classes had no clear connection between language teaching and students’ particular backgrounds. Community-based Pedagogy demonstrated to be an effective approach that facilitated students’ English learning in a meaningful path. The authenticity of the content and the strategies implemented which integrated local knowledge and the students’ familiar experiences, represented huge opportunities; while the passive participation of the community was a challenge found.